2013
DOI: 10.1007/978-3-642-54092-9_9
|View full text |Cite
|
Sign up to set email alerts
|

Research in Global Software Engineering: A Systematic Snapshot

Abstract: Abstract. This paper reports our extended analysis of the recent literature addressing global software engineering (GSE), using a new Systematic Snapshot Mapping (SSM) technique. The primary purpose of this work is to understand what issues are being addressed and how research is being carried out in GSEand comparatively, what work is not being conducted. We carried out the analysis in two stages. In the first stage we analyzed 275 papers published between January 2011 and June 2012, and in the second stage we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In conducting their analysis Butler et al [7] categorized 116 articles based upon the focus of attention of GSE projects and found that just 2 of those articles were related to the transition phase. This finding coincides with the results of a systematic snapshot mapping study which categorized 301 articles across various dimensions and found that only 19 were related to transition [8]. This suggests that researchers have focused more on establishing the drivers behind outsourcing while less attention has been given to issues relating to the switching of vendors and/or transition of software systems.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…In conducting their analysis Butler et al [7] categorized 116 articles based upon the focus of attention of GSE projects and found that just 2 of those articles were related to the transition phase. This finding coincides with the results of a systematic snapshot mapping study which categorized 301 articles across various dimensions and found that only 19 were related to transition [8]. This suggests that researchers have focused more on establishing the drivers behind outsourcing while less attention has been given to issues relating to the switching of vendors and/or transition of software systems.…”
Section: Introductionsupporting
confidence: 82%
“…In general the need for case study research arises out of a desire to understand a complex phenomenon and to focus on a specific instance or 'case' while retaining an holistic and real-world perspective [14]. Case studies have been increasingly adopted in software engineering in general and in Global Software Engineering in particular -prior research [8] has found that the most dominant methods used in GSE-related research are field and case studies and interviews. Choosing a particular research method implies making a trade-off between level of control and degree of realism.…”
Section: Research Methods and Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Inotherwords,packagedsoftware(PS)hasformedasignificantvalueintheworldofeconomics. Moreover,softwarepackagingvendorshaveconsiderablecompetitionamongthemtobeconsistent withtheirnewestproductupdatesseekingtofulfilcustomers'satisfactionaccordingtothefeatures andalsothecostsinPSmarket.Inthispaper,wefollowedavariantofthestructuralproceduresof ourSystematicSnapshotMapping(SSM)methodisderivedfromRaza (Raza,MacDonell,&Clear, 2013)systematicsnapshot,andHaddaraliteraturereviews (Haddara&Zach,2012).…”
Section: Introductionmentioning
confidence: 99%